2021
DOI: 10.3389/fphar.2021.700696
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Proteomics and Metabolomics Link Acne to the Action Mechanisms of Cryptotanshinone Intervention

Abstract: The label-free methods of proteomic combined with metabolomics were applied to explore the mechanisms of Cryptotanshinone (CPT) intervention in rats with acne. The model group consisted of rats given oleic acid (MC), then treated with CPT, while control groups did not receive treatment. The skin samples were significantly different between control, model and CPT-treated groups in hierarchical clustering dendrogram. Obvious separations of the skin metabolic profiles from the three groups were found through PCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 61 publications
1
9
0
1
Order By: Relevance
“…Several other dermatological conditions have recently been studied from the metabolomic point of view, including inflammatory infectious and neoplastic conditions [ 80 , 89 , 104 , 106 ]. Increased levels of L-glutamate have been found in skin samples of cutaneous T cell lymphomas and adjacent skin, together with decreased adenosine monophosphate [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several other dermatological conditions have recently been studied from the metabolomic point of view, including inflammatory infectious and neoplastic conditions [ 80 , 89 , 104 , 106 ]. Increased levels of L-glutamate have been found in skin samples of cutaneous T cell lymphomas and adjacent skin, together with decreased adenosine monophosphate [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the relationship between SCD and AMPK, a study showed that inhibition of SCD1 in cancer cells promoted the activation of AMPK and the subsequent reduction of glucose-mediated lipogenesis ( Scaglia et al, 2009 ). In addition, an integrated proteomic and metabolomic research on CTS in treating acne showed that CTS remedies abnormalities in unsaturated fatty acid synthetic enzymes and metabolites ( Zhu et al, 2021 ). Therefore, it is possible that CTS modulates lipid and fatty acid metabolism in resistant cancer cells by regulating the SCD and AMPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillosis merupakan suatu kelompok mikosis yang disebabkan oleh infeksi jamur spesies Aspergillus yaitu Aspergillus fumigatus (Bertuzzi et al, 2021;Zhu et al, 2021). Jamur Aspergillus fumigatus merupakan penyebab infeksi pada manusia yang terbanyak, dimana > 90% menyebabkan invasif dan noninvasif aspergillosis.…”
Section: Pendahuluanunclassified